Learning Strategy of Role Playing in The Material Submission of The Nuclear Power Application Environmental Physics Subjects - Legowo, Budi (International Journal of Active Learning, 2016)
Establishment controversy of the Nuclear Power Plant (NPP) that is delivered in the Environmental Physics course of Department of Physics of Faculty of Mathematic and Natural Science of Sebelas Maret University use the Role Playing strategy. This strategy brings active student playing the role of the government (policy makers), a group of scientists (neutral) and community groups who refused. Literature studies and group discussions conducted by its students to summarize back knowledge of nuclear power plants, according to the role that will be presented in lectures. The course made in the form of an open debate, where the lecturer acts as a moderator / facilitator. This strategy encourages students to hone the skills of independent learning (individual or group) and can help students to appreciate his knowledge either in small discussion (group) as well as the delivery of openly (public debate).How to CiteLegowo, B. (2016). Learning Strategy of Role Playing in The Material Submission of The Nuclear Power Application Environmental Physics Subjects. International Journal of Active Learning, 1(1).